Understanding maternal breastfeeding through the experiences lived by the breastfed baby - Mirella Teixeira Joca; Rafaelle Lopes de Oliveira; Régia Christina Moura Barbosa; Ana Karina Bezerra Pinheiro (Rev Rene)
The support service aims at tending to the needs of the breastfed baby. Our aim was to assess situations that create difficulties to the women’s health in the maternal breast-feeding period, to produce theoretic and methodological knowledge which can make possible better nursing care for the breastfed baby. Quantitative-qualitative research developed in the Natural Childbirth Center at Universidade Federal do Ceará. We verified health and life history, obstetrical, gynecological and family structure in forty (40) pregnant women’s charts. We verified that their have a family income, that they are housewives on households of six people, that seven of them had a probable childbirth date (PCD) for February/2004, and sixteen were primiparae. We selected 26 pregnant women, with PCD for the beginning of 2004, to be interviewed in the puerperium period through questions related to the difficulties and social support. The interviews were recorded, categorized and analyzed. We highlighted in the ‘living the puerperium’ category, as a positive aspect, the support from their families, and as a negative aspect the difficulties in assuming the role of mother. Therefore, social support is extremely important for the breast-feeding woman assume the role of mother.